The role of exopolymers in Sphingomonas paucimobilis attachment and biofilm formation - Azeredo, Joana (2001)
Exopolymers have an important role in biofilm formation, being involved in the initial adhesion events and influencing the biofilm characteristics. The results of a study with a strain of Sphingomonas paucimobilis that excretes a polysaccharide gum (gellan) has been used to exemplify the role of exopolymers in cell attachement and biofilm formation. The attachement results were interpreted throught the XDLVO theory and they revealed that exopolymers have a dual role in cell attachement by booth coating the substratum making adhesion favourable and by strengthing adeshion through the establishement of polymeric bridges. Exopolymers were also essential to the formation of Sphingomonas paucimobilis biofilms acting as scaffolds for bacterial proliferation. The physicochemical properties, the composition of the biofilm matrix and the cohesion forces within the biofilm were also conditioned by the presence of exopolymers.